Scheduling Subject used Genetical Algoritms (Case Studies: SMP Negeri 1 Delitua) - Siti Afifah Siregar; Rakhmat Kurniawan R; Suhardi Suhardi (Jurnal Mantik, 2024)
It is known that the preparation of subject scheduling at SMP Negeri 1 Deli Tua has gone through a process that is less efficient and effective due to several long procedures such as dividing study hours, adjusting teaching hours, and allowing for similarities in teaching hours or clashes between teaching hours. A genetic algorithm is an optimization technique whose working method imitates the process of evolution and changes in genetic structure in living things. The research aims to apply genetic algorithms to the subject scheduling system at SMP Negeri 1 Delitua. Research was conducted at SMP Negeri 1 Deli Tua. This research has used a genetic algorithm using the roulette wheel method and a GUI (Graphic User Interface) created with PHP and MySQL. The research results show that the application of genetic algorithms in scheduling systems can make scheduling more accurate and in a shorter time, with a mutation probability of 3.6 = 4 genes